Effect of the specific proteasome inhibitor bortezomib on cancer‐related muscle wasting. Issue 3 (7th July 2015) - Penna, Fabio; Bonetto, Andrea; Aversa, Zaira; Minero, Valerio Giacomo; Rossi Fanelli, Filippo; Costelli, Paola; Muscaritoli, Maurizio
Abstract: Background: Muscle wasting, a prominent feature of cancer cachexia, is mainly caused by sustained protein hypercatabolism. The enhanced muscle protein degradation rates rely on the activity of different proteolytic systems, although the Adenosine triphosphate (ATP)‐ubiquitin‐proteasome‐dependent pathway and autophagy have been shown to play a pivotal role. Bortezomib is a potent reversible and selective proteasome and NF‐κB inhibitor approved for the clinical use, which has been shown to be effective in preventing muscle wasting in different catabolic conditions. The aim of the present study has been to investigate whether pharmacological inhibition of proteasome by bortezomib may prevent skeletal muscle wasting in experimental cancer cachexia. Methods: Cancer cachexia was induced in rats by intraperitoneal injection of Yoshida AH‐130 ascites hepatoma cells and in mice by subcutaneous inoculation of C26 carcinoma cells. Animals were then further randomized to receive bortezomib. The AH‐130 hosts were weighted and sacrificed under anaesthesia, on Days 3, 4, 5, and 7 after tumour inoculation, while C26‐bearing mice were weighted and sacrificed under anaesthesia 12 days after tumour transplantation. NF‐κB and proteasome activation, MuRF1 and atrogin‐1 mRNA expression and beclin‐1 protein levels were evaluated in the gastrocnemius of controls and AH‐130 hosts. Results: Bortezomib administration in the AH‐130 hosts, although able to reduce proteasome and NF‐κB DNA‐binding activity in the skeletal muscle on Day 7 after tumour transplantation, did not prevent body weight loss and muscle wasting. In addition, bortezomib exerted a transient toxicity, as evidenced by the reduced food intake and by the increase in NF‐κB DNA‐binding activity in the AH‐130 hosts 3 days after tumour transplantation. Beclin‐1 protein levels were increased by bortezomib treatment in Day 3 controls but were unchanged on both Days 3 and 7 in the AH‐130 hosts, suggesting that an early compensatory induction of autophagy may exist in healthy but not in tumour‐bearing animals. Regarding C26‐bearing mice, bortezomib did not prevent as well body and muscle weight loss 12 days after tumour implantation. Conclusions: The results obtained suggest that proteasome inhibition by bortezomib is not able to prevent muscle wasting in experimental cancer cachexia. Further studies are needed to address the issue whether a different dosage of bortezomib alone or in combination with other drugs modulating different molecular pathways may effectively prevent muscle wasting during cancer cachexia.